Tourism Transformation as a Driver of Increasing Regional Original Income in Majene Regency in 2025 - Syahrinullah Syahrinullah (Economic: Journal Economic and Business, 2025)
This study aims to analyze how the transformation of the tourism sector can play a key role in increasing Regional Original Income (PAD) in Majene Regency. The urgency of this research lies in the need to strengthen the role of tourism as a primary source of PAD amidst increasingly fierce competition among regional and national tourist destinations. Majene Regency has rich natural, cultural, and maritime tourism potential, but it has not been managed optimally and sustainably. The research method uses a qualitative approach with data collection techniques through in-depth interviews, field observations, and policy document reviews. Data analysis is conducted thematically to identify patterns, relationships, and key themes related to the potential, obstacles, and strategies for regional tourism development. The results show that tourism transformation in Majene requires synergy between the local government, business actors, and the community in managing local potential in a sustainable, innovative, and inclusive manner. The resulting recommendations emphasize the importance of tourism governance reform, improving supporting infrastructure, and implementing policies based on community participation. Thus, tourism transformation is expected to be a catalyst for increasing PAD while strengthening the regional economic foundation towards competitive and sustainable development.